Hepatoprotective Activity of Borreria articularis (Linn.) against Paracetamol Induced Liver Damage in Rats - CHITRA, M.; MOHAMED FAROOK, N.A.; NALINI, R.; MOZHIARASI, P. (Asian Journal of Chemistry, 2010)
The hepatoprotective activity of Borreria articularis was studied on paracetamol induced hepatic damage in rats. The hepatic damage was studied by assessing the biochemical parameters like serum total bilirubin, total protein, alanine transaminase, aspartate transaminase and alkaline phosphatase. Treatment with aqueous extract of Borreria articularis was found to protect the rats from hepato-toxic action of paracetamol as evidenced by significant reduction in the elevated serum transaminase levels. The hepatoprotective activity was also supported by histopathological studies of liver tissue.